A look at trails through the pangenome visualization jungle - Durant, Éloi; Sabot, François; Conte, Matthieu; Rouard, Mathieu (2021)
High-throughput sequencing technologies enabled the production of multiple reference genome sequences for a single species. Comparisons of such sequences showed that there are structural variations between individuals from the same species such as Copy Number Variations (CNV) and Presence Absence Variations (PAV) that can have a significant impact on phenotypic variation in plants and could be suitable for breeding improved crop varieties. Thus, a single reference genome is insufficient to capture all variations. Pangenomics is an integrative approach which aims to the assessment of such genomic variations and more within a group of closely related individuals. Its definition can focus on the whole repertoire of genes within a group or can include blocks of genomic sequences shared between species. We introduce here a new visualization tool, based on a linear representation: the PANgenome Analyzer with CHromosomal Exploration (PANACHE). It is a web-based application which enables its users to explore a pangenomic reference divided in multiple panchromosomes.